Data portability among online platforms - Barbara Engels (Internet Policy Review, 2016)
This paper examines the competition effects of data portability among online platforms, providing policy recommendations for the preservation of innovative, undistorted competitive markets. Based on a platform-data model, it is illustrated how users, data and the products of a platform are related. Platform markets which entail an especially high risk of market power abuse are determined. It is concluded that the right to data portability as in the EU's General Data Protection Regulation has to be interpreted in a nuanced fashion in order to avoid adverse effects on competition and innovation.
Keywords: 300; Data protection; Competition law; Digital market